A case of complete atrioventricular block with extremely high blood concentration of azelnidipine - Naohito Ide; Ayaka Mochizuki; Yoshiyuki Kagawa; Masaharu Ito (BMC, 2021)
Abstract Background Azelnidipine, a dihydropyridine calcium channel blocker (CCB), has less adverse effects (e.g. hot flushes and reflex tachycardia) compared to other dihydropyridine CCBs. Azelnidipine has been reported to reduce heart rate as opposed to inducing tachycardia. No evidence of bradycardia or complete atrioventricular block (CAVB) with azelnidipine treatment has been reported. Case presentation In the present study, a 92-year-old woman was diagnosed with CAVB while taking azelnidipine and simvastatin for an extended period of time, and referred to our medical center. It was thought that the CAVB may have been an adverse effect of azelnidipine treatment. Specifically, it was considered that in this patient, one of the causes might be the concomitant use of simvastatin inhibiting the metabolism of azelnidipine by cytochrome P450 enzyme 3A4. Consequently, it was suggested to the patient's physician that the patient's serum azelnidipine levels be measured and treatment with azelnidipine and simvastatin be discontinued. The patient's serum concentration of azelnidipine at the time of her visit to our center was 63.4 ng/mL, higher than the normal acceptable level. There was no occurrence of CAVB for 4 weeks, to present, following discontinuation of azelnidipine and simvastatin treatment. Conclusions Azelnidipine has a different mechanism of action that other CCBs. In very rare cases, it may cause CAVB when combined with CYP3A4 inhibitors. If a patient taking azelnidipine is diagnosed with CAVB, physicians should suspect that the condition may be an adverse effect of azelnidipine and should consider discontinuing azelnidipine. And, in the elderly, it is necessary to avoid concomitant use of CYP3A4 inhibitors.